Cloning, Expression, and Characterization of a Novel Thermophilic Monofunctional Catalase from Geobacillus sp. CHB1. (7th August 2016) - Jia, Xianbo; Chen, Jichen; Lin, Chenqiang; Lin, Xinjian
Abstract : Catalases are widely used in many scientific areas. A catalase gene ( Kat ) from Geobacillus sp. CHB1 encoding a monofunctional catalase was cloned and recombinant expressed in Escherichia coli ( E. coli ), which was the first time to clone and express this type of catalase of genus Geobacillus strains as far as we know. This Kat gene was 1, 467 bp in length and encoded a catalase with 488 amino acid residuals, which is only 81% similar to the previously studied Bacillus sp. catalase in terms of amino acid sequence. Recombinant catalase was highly soluble in E. coli and made up 30% of the total E. coli protein. Fermentation broth of the recombinant E. coli showed a high catalase activity level up to 35, 831 U/mL which was only lower than recombinant Bacillus sp. WSHDZ-01 among the reported catalase production strains. The purified recombinant catalase had a specific activity of 40, 526 U/mg and K m of 51.1 mM. The optimal reaction temperature of this recombinant enzyme was 60°C to 70°C, and it exhibited high activity over a wide range of reaction temperatures, ranging from 10°C to 90°C. The enzyme retained 94.7% of its residual activity after incubation at 60°C for 1 hour. High yield and excellent thermophilic properties are valuable features for this catalase in industrial applications.